Impact of Covid-19 on Investors Herding Behavior: Evidence from Stock Market - Sharma, Sushil; Khanal, Khageshyor (KIC International Journal of Social Science and Management, 2023)
The purpose of this research was to use a descriptive and causal-comparative approach to analyze herding behavior in the Nepalese stock market during the COVID-19 epidemic. The study employed a regression model and a cross-sectional standard deviation (CSSD) index to evaluate the herding tendency. The investigation covers a significant time period from January 1, 2018, to February 28, 2023, and involves a substantial number of observation sessions totaling 1103. It appears that there is currently no evidence to suggest that herding behavior has occurred before, during, or after the COVID-19 pandemic. This study indicates that market participants were making independent decisions based on their own analysis and assessment of the situation during the pandemic, rather than relying on the actions or decisions of others.